Hyperglycosylated hCG and Placenta Accreta Spectrum - Einerson, Brett D.; Straubhar, Alli; Soisson, Sean; Szczotka, Kathryn; Dodson, Mark K.; Silver, Robert M.; Soisson, Andrew P. (American Journal of Perinatology, 2019)
Objective We aimed to evaluate the relationship between hyperglycosylated human chorionic gonadotropin (hCG-H) and placenta accreta spectrum (PAS) in the second and third trimesters of pregnancy.Study Design This was a case–control study of PAS and controls. hCG-H was measured in the second and third trimesters of pregnancy in women with pathologically confirmed cases of PAS and in gestational age-matched controls without PAS. We compared serum hCG-H levels in cases and controls, calculated summary statistics for diagnostic accuracy, and used receiver operating characteristic (ROC) curves to define an optimal cut-point for diagnosis of PAS using hCG-H.Results Thirty case samples and 30 control samples were evaluated for hCG-H. Mean hCG-H was lower in the case compared with control group (7.8 ± 5.9 μg/L vs. 11.8 ± 8.8 μg/L, p = 0.03). At an optimal cut-point for hCG-H of ≤7.6 μg/L, the sensitivity, specificity, positive likelihood ratios, negative likelihood ratios, and area under the ROC curve were 66.7%, 69.7%, 2.20%, 0.48%, and 0.68%, respectively.Conclusion Hyperglycosylated hCG levels in the second and third trimesters of pregnancy were lower in patients with PAS than in controls, but hCG-H showed only modest capability as a diagnostic test for PAS.
Keywords: hyperglycosylated hCG; biomarkers; placenta accreta spectrum; pregnancy